Spain : IOSCO Objectives and Principles of Securities Regulation: Detailed Assessment Implementation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper assesses implementation of the International Organization of Securities Commissions' (IOSCO) objectives and principles of securities regulation in Spain. Spain exhibits a high level of implementation of principles. The legal framework is robust and provides the Comision Nacional de Valores (CNMV) with broad supervisory, investigative, and enforcement powers. Arrangements for off-site monitoring of regulated entities are robust. However, some areas of supervision and enforcement require strengthening. In particular, the CNMV should make more use of on-site inspections for all types of investment service providers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet